Geração de energia elétrica domiciliar solar e eólica: análise das condições socioeconômicas para implantação em residências de baixo consumo - Ciamponi, Celso Eduardo Souza (Universidade Federal de São Carlos, 2015)
This paper presents the results of the economic feasibility analysis of implementing a distributed generation system based on electricity produced from wind and / or solar systems in the cities of Sorocaba, São Paulo; Brasilia, Federal District; Rio Branco, Acre; Porto Alegre, Rio Grande do Sul; Manaus, Amazonas and Fortaleza, Ceará. Thus, three scenarios were raised as well as the consumption of energy generated, in full or having to be complemented with the use of the normal distribution network. For each of the scenarios considered the following indicators were raised: NPV, IRR, and Payback final balance in the life of the equipment, based on a TMA equal to the government Selic rate. As a result we had a payback between 8 and 12 years in the best case scenario and between 12 and 16 years in the worst scenario analyzed, but all were positive NPV and final balance at the end of life of equipamrnto In this way it was possible to determine for these cities that the best structure to be implemented and serve as a basis for analyzing the implementation of this same infrastructure in other locations in Brazil, particularly in more remote places where access to electrification in the centralized system becomes more difficult to arrival.
Generation of solar and wind home eletricity: analysis of socioeconomic conditions for deployment in low-energy homes
Keywords: Energia elétrica; Energia - fontes alternativas; Política energética; Energy policy; Electric power; Renewable energy sources; OUTROS